An Efficient Rock Physics Scheme for Estimating Crack Density and Fluid Saturation of Shale Gas Reservoir - Jiang, Ziran; Qi, Qiaomu; Jiang, Xudong; Meng, Jikun; Wang, Xing-Jian (Frontiers in Earth Science, 2022)
We propose a simple rock physics model for the characterization of elastic properties of shale. The model combines a dual-porosity concept and the effective medium theory for constructing the anisotropic elastic tensor of the multimineral organic-rich shale. Based on the model, we address how to estimate two key shale gas evaluation parameters, i.e., crack density and gas saturation from well-log and seismic data. Application to Wufeng-Longmaxi Shale shows that the estimated crack porosity decreases with increasing burial depth and decreasing clay content. The analysis indicates that the microcracks are mainly developed among clay minerals, which is consistent with the results from mercury injection and SEM imaging experiments. More importantly, we show that the velocity of the Wufeng-Longmaxi Shale is primarily controlled by the crack porosity instead of the total porosity. Both P- and S-wave velocities decrease linearly as the volume of microcrack increases. The fluid substitution analysis shows that the Poisson's ratio and P-impedance of the shale are sensitive to the change of pore-fluid saturation. Based on the above sensitivity analyses, we customize a rock physics template for quantifying crack density and gas saturation from the shale elastic properties. The interpretation results show that there is an overall good agreement between the measured and predicted petrophysical properties from well-log and seismic data.